Optimizing Digital Marketing in Hospitality Industries - Rahul Bhandari; Muhamad Viktor A Sin (Startupreneur Business Digital (SABDA Journal), 2023)
Digital marketing is currently an important aspect of the hospitality industry as it allows hotels to reach out and connect with potential guests as they spend most of their time digitally. Currently, not all hotels take advantage to spend their money on annual budgets to make digital marketing strategies more effective, such as social media, which only makes promotions without any interaction with their followers, Search Engine Optimizer investment, and online hotel review. In the competitive hospitality industry, a strong digital presence is critical to attracting and retaining customers. Hotels can use a variety of digital marketing strategies to grow their business and capture the attention of potential guests. This study uses different digital marketing strategies to do business with different social media platforms and uses the medium of search engine optimization (SEO) to optimize websites and content for specific keywords. Digital marketing is a powerful tool for hotels looking to attract and retain customers in the digital age. The main objective of the magazine is to outline digital marketing strategies for the different target groups of hotels and the most diverse tourism players. By utilizing the various channels and digital technologies available, hotels can effectively reach and engage with their audience and drive business growth.